Analysis of Socio Demographic and Welfare of the People of Pemalang Based on Differences in Livelihood Economic Sector - Arsyadi, Shalahudin Alfian; Arif, Muhammad (Prosiding University Research Colloquium, 2022)
This research was conducted to measure the level of welfare of the village community in the Taman District, Pemalang Regency by conducting a survey of respondents based on the livelihoods of the Village community in the Taman District, Pemalang Regency and measuring the level of consumption, distribution of income and expenditure as well as family responsibilities in the community and socio-demographics of the village with the eyes existing livelihoods in Asemdoyong Village with a livelihood as fishermen, Cibelok Village as Rice Rice Farmers, Penggarit Village as Mango Plantation Farmers and Beji Village with a livelihood as traders based on the level of community income and family economic conditions as measured by Slovin analysis to calculate the population which will be used as respondents, the Gini Index to measure the distribution of community income and expenditure and the Lorenz Curve to measure the cumulative distribution of the proportion of community income in the 4 villages. From the results of the study, the Gini Index of income approaches shows that Taman District has a high income inequality with a value of 0.989 (high inequality), the inequality is obtained from 4 villages that are the survey objectives, including Beji Village 0.076 (low inequality), Asemdoyong Village 0.027 (Low inequality). . Cibelok Village 0.001 (Low Inequality and Penggarit Village 0.000 (Perfectly Evenly). The Gini Index for the expenditure approach of Taman District with a value of 0.996 (High Inequality). Beji Village 0.989 (High Inequality), Penggarit Village 0.130 (low inequality). Cibelok Village 0.121 (Inequality is high). low) and Asemdoyong Village 0.068 (low inequality) with food expenditure 0.201 and Non-Food 0.226 from these 4. For the Lorenz curve the income approach of Beji Village with a value of 0.076, Asemdoyong Village with a value of 0.027, Cibelok Village with a value of 0.001 and Penggarit Village with value 0.000.